Oil Shale Blasting Simulations Employing State-of-the-Art (2006) Computer Hydro-Codes and Constitutive Models - Dale Preece (International Society of Explosives Engineers, 2007)
In the late 1970’s and early 1980’s substantial resources were devoted to research focused on producing oil from the vast oil shale reserves in the western United States. Since the oil is solidified in the pore space of the shale, extracting it in production level quantities presented monumental technical challenges. Major advances were made in the methods used to extract oil from the shale in large quantities. Extraction methods evolved to culminate in the underground in-situ retorting process. In-situ retorting relied on explosive blasting of the shale to fragment the rock and induce sufficient porosity and permeability for a burn front to propagate through the oil shale. That burn front consumes some of the oil and liberates a substantial portion of it (~30%) for collection and further processing. Oil shale retorting is a blasting intensive process where the entire retort is rubblized in one very large, delay timed blast. Retort 7 in Western Colorado consumed 540,857 lb of slurry explosive to rubblized 348,940 tons of oil shale. Current rock blasting fragmentation predictive capabilities have evolved substantially since these retorts were designed and tested. It is the purpose of this study to simulate the explosively induced fragmentation of oil shale using state-of-the-art computer codes and material models and to infer retort design implications for future development.